174k views
0 votes
Simplify the following 6b-8(46 - 9) + 3b​

2 Answers

4 votes

Answer: 9b-296

Explanation:

Subtract the numbers 6−8 (46−9)+3 6−8(37)+3 2

Multiply the numbers 6−8⋅37+3 6−296+3

Combine like terms 6b−296+3b

Ur answer

9b−296

User Volley
by
6.6k points
6 votes

The value of 6b-8(46 - 9) + 3b is 9b - 296.

The equation given is 6b-8(46 - 9) + 3b, the calculation will go thus:

= 6b-8 (46 - 9) + 3b

= 6b-8 (46 - 9) + 3b

= 6b - 8(37) + 3b

= 6b - 296 + 3b

= 6b + 3b - 296

= 9b - 296

User Ravenspoint
by
6.6k points